Rhodopsin flash photolysis in man. - Pugh, E N (1975)
1. Human rhodopsin in vivo was flash bleached by a 600 musec xenon flash which could deliver to the retina up to 15 rod-equivalent quanta per rhodopsin molecule, and the fraction bleached measured by fundus reflexion densitometry. 2. The curve relating fraction rhodopsin bleached to intensity of flash saturates at 0.5 to 0.6. Thus, 40-50% of the rhodopsin is left photo-regenerated by the brightest flashes. 3. Three types of densitometry experiments confirm the saturation of the bleaching curve. 4. The kinetic constants required to account for the observed photo-regeneration were somewhat discrepant with in vitro and in situ estimates from infrahuman species. Specifically, (i) the quantum efficiency of the back reaction, metarhodopsin I hv leads to rhodopsin, was inferred to be nearly as high as that of the forward reaction; and (ii) the rate of the metarhodopsin I leads to metarhodopsin II dark reaction was inferred to be less than 500 sec(-1).